A π‐Conjugated Polyimide‐Based High‐Performance Aqueous Potassium‐Ion Asymmetric Supercapacitor. Issue 15 (4th May 2022) - Zhao, Yaoyao; Zhang, Shicong; Xu, Shumao; Li, Xiao; Zhang, Yifan; Xu, Yang; Zhou, Jian; Bi, Hui; Huang, Fuqiang; Lin, Tianquan
Abstract: Aqueous asymmetric supercapacitor has captured widespread attention as a sustainable high‐power energy resource. Organic electrode materials are appealing owing to their sustainability and high redox reactivity, but suffer from structural instability and low power density. Here the π ‐conjugated polyimide‐based organic electrodes with different lengths of alkyl chains are explored to achieve high rate capability and long lifespan in an aqueous K + ‐ion electrolyte. The fabricated asymmetric supercapacitor exhibits high capacities of 107 mAh g −1 at 2 A g −1 and 67 mAh g −1 at 90 A g −1 . A specific capacity of 65 mAh g −1 over 70% of the initial performance is obtained after 65 000 cycles. Molecular engineering of long alkyl chains in polyimide can reduce the degree of π ‐conjugation and spatially block the π ‐conjugated imide bond with limited redox activity but improved stability against chemical degradation. Further electrochemical quartz crystal microbalance, ex‐situ Fourier transformed infrared spectroscopy, and X‐ray photoelectron spectroscopy characterizations reveal the pseudocapacitance behavior originating from the π ‐conjugated polyimide‐based redox reaction with potassium ions and hydrated potassium ions. A promising polyimide‐based polymer with extended π ‐conjugated system for high‐performance asymmetric supercapacitor is showcased. Abstract : Molecular engineering of new conducing polymers with extended π‐conjugated system is crucial for polymer‐based pseudocapacitors with high high‐rate performance and long lifespan. The developed large π‐conjugated polyimide with improved redox activity and enhanced stability against chemical degradation renders it a promising electrode material for supercapacitors with improved cycling stability and energy densities (107 mAh g −1 at 2 A g −1 ).